Hybrid Renewable Energy System: Design of Fishing Boat Lamp Based on Solar Energy and Seawater Electrochemistry in West Kalimantan - Santoso, Hendi; Utami, Naniek Tri (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
This study presents the design and performance evaluation of a Hybrid Renewable Energy System (HRES) integrating a mini solar panel, lithium-ion battery, and seawater-based galvanic cell (Mg–Cu) for sustainable lighting applications on small fishing boats in coastal West Kalimantan, Indonesia. The system aims to provide an affordable and renewable power source for traditional fishermen. Experimental results show that a 2 W mini solar panel produced an average of 12.64 Wh/day with a peak output of 2.7 W under optimal sunlight conditions. The lithium-ion 3S 18650 battery pack (27 Wh) demonstrated stable performance, powering a 3 W HPL lamp continuously for 12 hours (18:00–06:00) with load voltage decreasing gradually from 3.36 V to 3.15 V and current from 0.78 A to 0.66 A, corresponding to a light intensity reduction from 2538 lux to 1882 lux at a 10 cm distance. In contrast, the Mg–Cu seawater cell produced lower illumination levels of 492–221 lux, indicating its suitability primarily as a backup energy source. The hybrid configuration effectively enhanced system reliability and operational sustainability in maritime environments. Overall, this study confirms the potential of HRES to strengthen energy independence among small-scale fishermen while supporting SDG 7 (Affordable and Clean Energy), SDG 13 (Climate Action), and SDG 14 (Life Below Water) through practical utilization of locally available renewable resources.